THE BEHAVIOR OF PARAMASAN DAYAK INDIGENOUS COMMUNITY IN PROTECTING THE ENVIRONMENT - Wardhani, Dyah Febria; Arisanty, Deasy; Nugroho, Agung; Utami, Umi Baroroh Lili (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
This research investigates the environmental conservation behaviours of the Dayak Paramasan community residing in the remote regions of Kalimantan, Indonesia. The study aims to explore the influence of deeply rooted cultural values on the community's practices related to environmental preservation. Employing a qualitative research approach, data will be collected through observational, participatory techniques and in-depth interviews with community members, indigenous leaders, and local policymakers. Secondary sources, including historical records and traditional documentation, will also be examined to provide a comprehensive context. Data analysis will involve transcription, thematic coding, and a conceptual framework to unveil the intricate connections between cultural values, actions, and attitudes concerning environmental conservation. The research seeks to enhance our understanding of the Dayak Paramasan community's engagement in environmental conservation and hopes to inform the development of sustainable and inclusive conservation approaches while preserving their valuable cultural heritage.